Lithium ion battery and negative electrode sheet
Patent Information
- Application Number
- CN202510438701.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2026-10-16
AI Technical Summary
N/P值过大,则正极会出现深度放电状态,经过长时间循环,正极材料会出现氧化、结构坍塌、析氧等安全隐患;另外N/P值过大,也会增加负极材料的使用量,使电池的整体的能量密度下降
[0017] Furthermore, the adhesive is at least one of sodium alginate, polyacrylic acid, styrene-butadiene rubber, and SONE.
Smart Images

Figure BDA0005350388770000101 
Figure BDA0005350388770000111
Abstract
Description
Technical Field
[0001] This application relates to the field of new energy, and in particular to a lithium-ion battery and a negative electrode. Background Technology
[0002] With the increasing global demand for renewable energy, lithium-ion batteries, as the primary energy storage device, are widely used in electric vehicles, mobile electronic devices, and large-scale energy storage. Improving the energy density of lithium-ion batteries has become one of the key technologies for enhancing battery performance and extending battery life. Currently, the energy density of lithium-ion batteries is constrained by several factors, including the performance limitations of the battery's positive and negative electrode materials, electrolyte, and separator.
[0003] Typically, lithium-ion batteries are designed with safety in mind, so the areal capacity of the negative electrode is greater than that of the positive electrode, meaning the N / P ratio is greater than 1. An excessively high N / P ratio can lead to deep discharge at the positive electrode, and after prolonged cycling, this can cause oxidation, structural collapse, and oxygen evolution in the positive electrode material, posing safety risks. Furthermore, a high N / P ratio also increases the amount of negative electrode material used, reducing the overall energy density of the battery. However, if the N / P ratio is less than 1, the negative electrode capacity is insufficient to fully absorb the lithium ions released from the positive electrode, potentially leading to lithium deposition, increasing the risk of short circuits, and affecting battery life and safety.
[0004] In view of the above, it is necessary to develop a lithium-ion battery and its negative electrode with low N / P value, high energy density and safety. Summary of the Invention
[0005] In view of the above problems, this application provides a lithium-ion battery with low N / P value, high energy density, and safety, as well as its negative electrode.
[0006] The first aspect of this application provides a lithium-ion battery negative electrode sheet, comprising:
[0007] A current collector;
[0008] An active layer located on the current collector; the active layer includes a negative electrode active material, an additive, a first conductive agent, a second conductive agent, a first dispersant, a second dispersant, and a binder; the additive has an affinity for lithium ions ≤0.9eV.
[0009] Unlike existing technologies, this application uses an additive with an affinity for lithium ions ≤0.9 eV as the material for the current collector active layer. Due to the additive's high lithium affinity, it can react with lithium at the negative electrode to form stable products, reducing the level of lithium metal nucleation. Furthermore, the formed products have high specific capacity, reducing the amount of negative electrode material used and achieving higher energy density. Simultaneously, it improves the diffusion rate of lithium ions, enhances the distribution of lithium ions and lithium metal, prevents lithium dendrite precipitation, and improves battery safety.
[0010] Furthermore, the particle size of the additive is 2-30 nm.
[0011] Furthermore, the additives include at least one of graphite, silicon, silicon-carbon composite material, lithium titanate, hard carbon, tin dioxide, iron oxide, tin-lithium alloy, lithium-aluminum alloy, silicon nitride, porous carbon, carbon nitride, polyaniline, polythiophene, manganese oxide, cobalt oxide, nickel oxide, copper, silver, beryllium, sodium, magnesium, aluminum, silicon, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, germanium, antimony, lead, yttrium, strontium, molybdenum, palladium, silver, and tungsten.
[0012] Furthermore, the negative electrode active material includes at least one of graphite carbon material, silicon-based material, tin-based alloy material, transition metal sulfide, transition metal nitride, metal oxide, metal sulfide, metal phosphide, metal nitride, metal boride, metal carbide, metal silicide, metal germanide, metal indiumide, metal bismuthide, metal vanadiumide, metal titanide, metal ironide, metal cobaltide, and metal nickelide.
[0013] Furthermore, the first conductive agent includes at least one of carbon black, graphite, multi-walled carbon nanotubes, polyaniline, polypyrrole, polystyrene, conductive rubber, fullerene, porous carbon, activated carbon, and nitrogen-doped carbon materials.
[0014] Furthermore, the second conductive agent includes at least one of single-walled carbon nanotubes, graphene, carbon fiber, and Ketjen black.
[0015] Furthermore, the first dispersant includes at least one of polyvinylpyrrolidone, sodium polyacrylate, polyvinyl alcohol, polyurethane, polyvinyl alcohol-aldehyde resin, sodium carboxymethyl cellulose, polyamino acid, polyvinyl chloride, tetrafluoroethylene, polyethylene, polypropylene, polystyrene, aminosilane, epoxy resin, acrylate, polyester, silane coupling agent, and vulcanized rubber.
[0016] Furthermore, the second dispersant includes at least one of the following: polycarboxylic acid dispersants, lignin sulfonate dispersants, naphthalene-based dispersants, aminosulfonate dispersants, sulfonated phenolic resin dispersants, vinyl ether dispersants, polymeric sulfonate dispersants, polyether dispersants, polyacrylamide, alkanolamine dispersants, polyether polyol dispersants, melamine dispersants, polyethylene ether dispersants, polyamino acid dispersants, sodium carbonate dispersants, and sulfate dispersants.
[0017] Furthermore, the adhesive is at least one of sodium alginate, polyacrylic acid, styrene-butadiene rubber, and SONE.
[0018] The second aspect of this application provides a lithium-ion battery, wherein the lithium-ion battery uses the lithium-ion battery negative electrode sheet described in the first aspect of this application.
[0019] Furthermore, the N / P value of the lithium-ion battery is 0.7-1.05.
[0020] Unlike existing technologies, the lithium-ion battery in this application has an N / P value of 0.7-1.05 and achieves a high energy density. During operation, the lithium-ion battery exhibits high lithium-ion diffusion rate at the negative electrode and uniform distribution of lithium ions and lithium metal; it enables rapid lithium-ion insertion at the negative electrode and avoids lithium dendrite precipitation.
[0021] The above description of the invention is merely an overview of the technical solution of this application. In order to enable those skilled in the art to better understand the technical solution of this application and to implement it based on the textual description, and to make the above-mentioned objectives and other objectives, features and advantages of this application easier to understand, the following description is based on the specific embodiments of this application. Detailed Implementation
[0022] To explain in detail the technical content, structural features, objectives, and effects of the technical solution, the following detailed description is provided in conjunction with specific embodiments.
[0023] To illustrate the possible application scenarios, technical principles, implementable specific solutions, and achievable objectives and effects of this application in detail, the following description is provided in conjunction with the specific embodiments listed. The embodiments described herein are merely illustrative of the technical solutions of this application and are therefore intended only as examples, not as limiting the scope of protection of this application.
[0024] In this document, the term "embodiment" means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment of this application. The term "embodiment" appearing in various places throughout the specification does not necessarily refer to the same embodiment, nor does it specifically limit its independence or connection with other embodiments. In principle, in this application, as long as there are no technical contradictions or conflicts, the technical features mentioned in each embodiment can be combined in any way to form corresponding implementable technical solutions.
[0025] Unless otherwise defined, the technical terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the use of related terms herein is merely for the purpose of describing particular embodiments and is not intended to limit this application.
[0026] In the description of this application, the term "and / or" is used to describe the logical relationship between objects, indicating that three relationships can exist. For example, A and / or B means: A exists, B exists, and A and B exist simultaneously. Additionally, the character " / " in this document generally indicates that the preceding and following objects have an "or" logical relationship.
[0027] In this application, terms such as “first” and “second” are used only to distinguish one entity or operation from another, and do not necessarily require or imply any actual quantity, hierarchy or order relationship between these entities or operations.
[0028] Unless otherwise specified, the use of terms such as “comprising,” “including,” “having,” or other similar expressions in this application is intended to cover non-exclusive inclusion, which does not exclude the presence of additional elements in a process, method, or product that includes the stated elements, such that a process, method, or product that includes a list of elements may include not only those defined elements but also other elements not expressly listed, or elements inherent to such a process, method, or product.
[0029] Similar to the understanding in the Examination Guidelines, in this application, expressions such as "greater than," "less than," and "exceeding" are understood to exclude the stated number; expressions such as "above," "below," and "within" are understood to include the stated number. Furthermore, in the description of the embodiments in this application, "multiple" means two or more (including two), and similar expressions related to "multiple" are also understood in this way, such as "multiple groups" and "multiple times," unless otherwise explicitly specified.
[0030] The first aspect of this application provides a lithium-ion battery negative electrode sheet, comprising:
[0031] A current collector;
[0032] An active layer located on the current collector; the active layer includes a negative electrode active material, an additive, a first conductive agent, a second conductive agent, a first dispersant, a second dispersant, and a binder; the additive has an affinity for lithium ions ≤0.9eV.
[0033] Unlike existing technologies, this application uses an additive with an affinity for lithium ions ≤0.9 eV as the material for the current collector active layer. Due to the additive's high lithium affinity, it can react with lithium at the negative electrode to form stable products, reducing the level of lithium metal nucleation. Furthermore, the formed products have high specific capacity, reducing the amount of negative electrode material used and achieving higher energy density. Simultaneously, it improves the diffusion rate of lithium ions, enhances the distribution of lithium ions and lithium metal, prevents lithium dendrite precipitation, and improves battery safety.
[0034] Furthermore, the particle size of the additive is 2-30 nm.
[0035] Furthermore, the additives include at least one of graphite, silicon, silicon-carbon composite material, lithium titanate, hard carbon, tin dioxide, iron oxide, tin-lithium alloy, lithium-aluminum alloy, silicon nitride, porous carbon, carbon nitride, polyaniline, polythiophene, manganese oxide, cobalt oxide, nickel oxide, copper, silver, beryllium, sodium, magnesium, aluminum, silicon, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, germanium, antimony, lead, yttrium, strontium, molybdenum, palladium, silver, and tungsten.
[0036] Furthermore, the additive is at least one of silver, aluminum, and magnesium metals.
[0037] Furthermore, the negative electrode active material includes at least one of graphite carbon material, silicon-based material, tin-based alloy material, transition metal sulfide, transition metal nitride, metal oxide, metal sulfide, metal phosphide, metal nitride, metal boride, metal carbide, metal silicide, metal germanide, metal indiumide, metal bismuthide, metal vanadiumide, metal titanide, metal ironide, metal cobaltide, and metal nickelide.
[0038] Furthermore, the negative electrode active material and the additive are different substances.
[0039] Furthermore, the first conductive agent includes at least one of carbon black, graphite, multi-walled carbon nanotubes, polyaniline, polypyrrole, polystyrene, conductive rubber, fullerene, porous carbon, activated carbon, and nitrogen-doped carbon materials.
[0040] Furthermore, the second conductive agent includes at least one of single-walled carbon nanotubes, graphene, carbon fiber, and Ketjen black. The second conductive agent, combined with additives, accelerates the electrochemical reaction, enabling rapid lithium-ion insertion into the negative electrode.
[0041] Furthermore, the first dispersant includes at least one of polyvinylpyrrolidone, sodium polyacrylate, polyvinyl alcohol, polyurethane, polyvinyl alcohol-aldehyde resin, sodium carboxymethyl cellulose, polyamino acid, polyvinyl chloride, tetrafluoroethylene, polyethylene, polypropylene, polystyrene, aminosilane, epoxy resin, acrylate, polyester, silane coupling agent, and vulcanized rubber.
[0042] Furthermore, the second dispersant includes at least one of the following: polycarboxylic acid dispersants, lignin sulfonate dispersants, naphthalene-based dispersants, aminosulfonate dispersants, sulfonated phenolic resin dispersants, vinyl ether dispersants, polymeric sulfonate dispersants, polyether dispersants, polyacrylamide, alkanolamine dispersants, polyether polyol dispersants, melamine dispersants, polyethylene ether dispersants, polyamino acid dispersants, sodium carbonate dispersants, and sulfate dispersants.
[0043] Furthermore, the adhesive is at least one of sodium alginate, polyacrylic acid, styrene-butadiene rubber (SBR), and SONE.
[0044] The second aspect of this application provides a lithium-ion battery, wherein the lithium-ion battery uses the lithium-ion battery negative electrode sheet described in the first aspect of this application.
[0045] Furthermore, the N / P value of the lithium-ion battery is 0.7-1.05.
[0046] Unlike existing technologies, the lithium-ion battery in this application has an N / P value of 0.7-1.05 and achieves a high energy density. During operation, the lithium-ion battery exhibits high lithium-ion diffusion rate at the negative electrode and uniform distribution of lithium ions and lithium metal; it enables rapid lithium-ion insertion at the negative electrode, avoids lithium dendrite precipitation, and ensures high battery safety.
[0047] In this embodiment, the N / P value is the capacity ratio of the negative electrode to the positive electrode. Influencing factors include material selection, electrode design parameters (coating amount, thickness), battery design strategy (safety redundancy), operating conditions (temperature, rate) and aging conditions.
[0048] In this embodiment, N / P control is achieved by selecting different materials and adjusting the loading of the negative electrode active material.
[0049] Example 1: Battery with an N / P value of 1.05
[0050] 1. Preparation of positive electrode:
[0051] Lithium iron phosphate (LFP), carbon black (SP), and polyvinylidene fluoride (PVDF) binder (mass ratio 95:3:2) were uniformly mixed in N-methyl-2-pyrrolidone (NMP). The mixture was then coated onto conductive-coated aluminum foil using a doctor blade and rolled and slit to form the positive electrode sheet. The single-sided loading of the LFP was 15.496 mg / cm². 2 Compacted density 2.6 g / cm³ 3 .
[0052] 2. Preparation of negative electrode sheet
[0053] The active layer components, including the negative electrode active material (graphite): first conductive agent (SP): first dispersant (CMC): binder SBR: additive (Ag): second dispersant (sodium lignosulfonate): second conductive agent (single-walled carbon nanotubes) in a ratio of 90.9:4:2:2:0.4:0.4:0.3, were mixed evenly in deionized water. The mixture was then coated onto a 6μm copper foil using a doctor blade and rolled and slit to form the negative electrode sheet. The silver metal additive had a particle size of 15nm and was added at a concentration of 0.4%. The single-sided loading of the negative electrode active material graphite was 6.579 mg / cm². 2 Compacted density 1.6 g / cm³ 3 The N / P ratio is 1.05.
[0054] The diaphragm used was a Celgard 2400 membrane, and the electrolyte was 1M lithium hexafluorophosphate (LiPF6) in ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 1:1 = 0.8), containing 5% fluoroethylene carbonate (FEC) additive, and the amount of electrolyte was approximately 2 g Ah-1.
[0055] Assemble the above components into a battery in the order of positive electrode, separator, and negative electrode, and test the voltage range of 2.5V-3.6V.
[0056] Examples 2-7
[0057] The difference between Examples 2-7 and Example 1 is that the loading (thickness) of the negative electrode active material is different.
[0058] The N / P ratios for Examples 2-7 are 1, 0.9, 0.8, 0.7, 0.6, and 0.5, respectively.
[0059] Example 8
[0060] The difference between Example 8 and Example 1 is that the content of the negative electrode active layer components is different, and the loading of the negative electrode active material is different; the N / P value of Example 8 is 0.9.
[0061] In Example 8, the ratio of negative electrode active material (graphite): first conductive agent (SP): first dispersant (CMC): binder SBR: additive (Ag): second dispersant (sodium lignosulfonate): second conductive agent (single-walled carbon nanotubes) is 91.45:4:2:2:0.2:0.2:0.15. The amount of silver metal added is 0.2%.
[0062] Example 9
[0063] The difference between Example 9 and Example 1 is that the content of the negative electrode active layer components is different, and the loading of the negative electrode active material is different; the N / P value of Example 9 is 0.9.
[0064] In Example 9, the ratio of negative electrode active material (graphite): first conductive agent (SP): first dispersant (CMC): binder SBR: additive (Ag): second dispersant (sodium lignosulfonate): second conductive agent (single-walled carbon nanotubes) is 90:3.5:2:2:1:1:0.5. The amount of silver metal added is 1%.
[0065] Example 10
[0066] The difference between Example 10 and Example 1 is that the particle size of the silver additive in the negative electrode active layer component is 5 nm, and the loading of the negative electrode active material is different; the N / P value of Example 10 is 0.9.
[0067] Example 11
[0068] The difference between Example 10 and Example 1 is that the particle size of the silver additive in the negative electrode active layer component is 30 nm, and the loading of the negative electrode active material is different; the N / P value of Example 11 is 0.9.
[0069] Example 12
[0070] The difference between Example 12 and Example 1 is that the additive in the negative electrode active layer component is aluminum, and the loading of the negative electrode active material is different; the N / P value of Example 12 is 0.9.
[0071] Example 13
[0072] The difference between Example 13 and Example 1 is that the additive in the negative electrode active layer component is aluminum, and the loading of the negative electrode active material is different; the N / P value of Example 13 is 0.5.
[0073] Example 14
[0074] The difference between Example 12 and Example 1 is that the additive in the negative electrode active layer component is magnesium, and the loading of the negative electrode active material is different; the N / P value of Example 14 is 0.9.
[0075] Example 15
[0076] The difference between Example 12 and Example 1 is that the additive in the negative electrode active layer component is magnesium, and the loading of the negative electrode active material is different; the N / P value of Example 15 is 0.5.
[0077] For example, a battery with an N / P value set to 1.05.
[0078] 1. Preparation of positive electrode:
[0079] Lithium iron phosphate (LFP), carbon black (SP), and polyvinylidene fluoride (PVDF) binder (mass ratio 95:3:2) were uniformly mixed in N-methyl-2-pyrrolidone (NMP). The mixture was then coated onto conductive-coated aluminum foil using a doctor blade and rolled and slit to form the positive electrode sheet. The single-sided loading of the LFP was 15.496 mg / cm². 2 Compacted density 2.6 g / cm³ 3 .
[0080] 2. Negative electrode preparation:
[0081] Graphite: Conductive Agent 1 [Carbon Black (SP)]:CMC:SBR = 90:5:2.5:2.5 was mixed evenly in deionized water and coated onto 6μm copper foil using a doctor blade. The mixture was then rolled and slit to form the negative electrode sheet. The single-sided loading of graphite was 6.579 mg / cm². 2 Compacted density 1.6 g / cm³ 3 .
[0082] The diaphragm used was a Celgard 2400 membrane, and the electrolyte was 1M lithium hexafluorophosphate (LiPF6) in ethylene carbonate (EC) and diethyl carbonate (DEC) (volume ratio 1:1 = 0.8), containing 5% fluoroethylene carbonate (FEC) additive, and the amount of electrolyte was approximately 2 g Ah-1.
[0083] Assemble the above components into a battery in the order of positive electrode, separator, and negative electrode, and test the voltage range of 2.5V-3.6V.
[0084] Performance testing:
[0085] The batteries prepared in the examples and comparative examples were subjected to the following tests:
[0086] 1. Electrode resistance: The ACFILM electrode resistance tester was used, with a test pressure of 0.2MPa and a unit of mΩ.
[0087] 2. Calculation of gravimetric energy density (Wh / kg):
[0088] Energy density = 1000 × battery capacity (mAh) × battery voltage (volts) / battery weight (kg). The results are shown in Table 1.
[0089] Table 1. Relevant parameters and test performance of batteries in Examples 1-15 and control examples.
[0090]
[0091]
[0092] The above experimental results show that:
[0093] Adding additives with high lithium coordination to the negative electrode effectively increases the negative electrode's lithium storage and adsorption capacity, reduces the NP value, improves the battery's energy density, and enhances battery safety.
[0094] Examples 1-15 all showed improved energy density compared to the control group, with Ag as the additive showing better results than Al and Mg. This is considered to be due to Ag's superior conductivity and lithiophilicity compared to Al and Mg. Silver metal particles were the preferred additive. Furthermore, the particle size of the additive significantly affected the additive effect; smaller particles resulted in a larger contact area, stronger lithiation ability, and were more conducive to lithium ion diffusion at the negative electrode and stable lithium deposition.
[0095] This application employs an additive with an affinity for lithium ions ≤0.9 eV as the material for the current collector active layer. Due to the additive's high lithium affinity, it can undergo an affinity reaction with lithium at the negative electrode to form a stable product, reducing the level of lithium metal nucleation. Furthermore, the formed product exhibits high specific capacity, reducing the amount of negative electrode material required and achieving higher energy density. Simultaneously, it improves the diffusion rate of lithium ions, enhances the distribution of lithium ions and lithium metal, prevents lithium dendrite precipitation, and improves battery safety.
[0096] Finally, it should be noted that although the above embodiments have been described in the description of this application, this should not limit the scope of patent protection of this application. Any technical solutions that are based on the essential concept of this application, utilize the content described in this application's description to make equivalent structural or procedural substitutions or modifications, or directly or indirectly implement the technical solutions of the above embodiments in other related technical fields, are all included within the scope of patent protection of this application.
Claims
1. A lithium-ion battery negative electrode sheet, characterized in that, include: A current collector; An active layer located on the current collector; the active layer includes a negative electrode active material, an additive, a first conductive agent, a second conductive agent, a first dispersant, a second dispersant, and a binder; The affinity of the additive for lithium ions is ≤0.9eV.
2. The battery negative electrode sheet according to claim 1, characterized in that, The particle size of the additive is 2-30 nm.
3. The battery negative electrode sheet according to claim 1, characterized in that, The additives include at least one of graphite, silicon, silicon-carbon composite material, lithium titanate, hard carbon, tin dioxide, iron oxide, tin-lithium alloy, lithium-aluminum alloy, silicon nitride, porous carbon, carbon nitride, polyaniline, polythiophene, manganese oxide, cobalt oxide, nickel oxide, copper, silver, beryllium, sodium, magnesium, aluminum, silicon, potassium, calcium, titanium, vanadium, chromium, manganese, iron, cobalt, nickel, copper, zinc, germanium, antimony, lead, yttrium, strontium, molybdenum, palladium, silver, and tungsten.
4. The battery negative electrode sheet according to claim 3, characterized in that, The additive is at least one of silver, aluminum, and magnesium metals.
5. The battery negative electrode sheet according to claim 1, characterized in that, The negative electrode active material includes at least one of graphite carbon material, silicon-based material, tin-based alloy material, transition metal sulfide, transition metal nitride, metal oxide, metal sulfide, metal phosphide, metal nitride, metal boride, metal carbide, metal silicide, metal germanide, metal indiumide, metal bismuthide, metal vanadiumide, metal titaniumide, metal ironide, metal cobaltide, and metal nickelide.
6. The battery negative electrode sheet according to claim 1, characterized in that, The first conductive agent includes at least one of carbon black, graphite, multi-walled carbon nanotubes, polyaniline, polypyrrole, polystyrene, conductive rubber, redox conductive agent, fullerene, porous carbon, activated carbon, and nitrogen-doped carbon materials; the second conductive agent includes at least one of single-walled carbon nanotubes, graphene, carbon fiber, and Ketjen black.
7. The battery negative electrode sheet according to claim 1, characterized in that, The first dispersant includes at least one of polyvinylpyrrolidone, sodium polyacrylate, polyvinyl alcohol, polyurethane, polyvinyl alcohol-aldehyde resin, sodium carboxymethyl cellulose, polyamino acid, polyvinyl chloride, tetrafluoroethylene, polyethylene, polypropylene, polystyrene, aminosilane, epoxy resin, acrylate, polyester, silane coupling agent, and vulcanized rubber; the second dispersant includes at least one of polycarboxylic acid dispersants, lignin sulfonate dispersants, naphthalene-based dispersants, aminosulfonate dispersants, sulfonated phenolic resin dispersants, vinyl ether dispersants, polysulfonate dispersants, polyether dispersants, polyacrylamide, alkanolamine dispersants, polyether polyol dispersants, melamine dispersants, polyvinyl ether dispersants, polyamino acid dispersants, sodium carbonate dispersants, and sulfate dispersants.
8. The battery negative electrode sheet according to claim 1, characterized in that, The adhesive is at least one of sodium alginate, polyacrylic acid, styrene-butadiene rubber, and SONE.
9. A lithium-ion battery, characterized in that, The lithium-ion battery uses the lithium-ion battery negative electrode sheet according to any one of claims 1-8.
10. The lithium-ion battery according to claim 1, characterized in that, The N / P value of the lithium-ion battery is 0.7-1.05.